2018
DOI: 10.1177/0021998318774401
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of quasi-static indentation and low-velocity impact on composite overwrapped pressure vessels

Abstract: The equivalence of quasi-static indentation and low-velocity impact loading regimes has been assessed for composite overwrapped pressure vessels. Test specimens were assessed in detail in terms of the force–displacement response, and micro-focus computed tomography was used for qualitative and quantitative assessment of the associated damage to the constituent materials/interfaces. The results show that the force–displacement response follows an essentially similar pattern between the two loading regimes (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This method is less complicated than low-velocity impact (LVI) since it does not have oscillations and requires a lower rate of data collecting. Several studies have consistently shown a strong correlation between quasi-static indentation in laminated composites and low-velocity impact damage [14][15][16]. This relationship was also confirmed in the current investigation [17].…”
Section: Introductionsupporting
confidence: 88%
“…This method is less complicated than low-velocity impact (LVI) since it does not have oscillations and requires a lower rate of data collecting. Several studies have consistently shown a strong correlation between quasi-static indentation in laminated composites and low-velocity impact damage [14][15][16]. This relationship was also confirmed in the current investigation [17].…”
Section: Introductionsupporting
confidence: 88%
“…The degree and area of damage caused by perforation to CFRP structures are much lower than that caused by impact. Therefore, indentation test was used to simulate the impact damage 50 . The QSI test was performed on a universal testing machine (LD24) at a speed of 1 mm/min as shown in Figure 2A.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, indentation test was used to simulate the impact damage. 50 The QSI test was performed on a universal testing machine (LD24) at a speed of 1 mm/ min as shown in Figure 2A. The tube was placed in the middle of the V-shaped support, followed by the test in the center of the tube.…”
Section: Quasi-static Indentation (Qsi) Testmentioning
confidence: 99%
“…Allen et al carried out an experimental study to compare the structural behavior of composite pressure vessels under quasi-static indentation and low velocity impact. According to their study, the damage occurring differs in terms of matrix failure, but the quasi-static indentation test can be considered an analogue for a low-velocity impact test on composite vessels [17]. Farhood et al investigated the impact behavior of carbon/basalt hybrid composite pipes in an experimental study.…”
Section: Introductionmentioning
confidence: 99%